(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Digital technologies are revolutionizing the accounting industry. This article is devoted to studying the positive and negative aspects of the introduction of technologies. Opportunities such as automation of the accounting system, real-time monitoring, increased data security, and time saving are highlighted. At the same time, cybersecurity risks, lack of qualified personnel, and difficulties associated with software updates are also discussed. The role of digital technologies in modern accounting is analyzed based on international experience and statistical data.